Disorders Related to PI3Kδ Hyperactivation: Characterizing the Clinical and Immunological Features of Activated PI3-Kinase Delta Syndromes - Redenbaugh, Vyanka; Coulter, Tanya (Frontiers in Pediatrics, 2021)
Phosphoinositide-3-kinase δ (PI3Kδ) is found in immune cells and is part of the PI3K/AKT/mTOR/S6K signalling pathway essential to cell survival, growth and differentiation. Hyperactivation of PI3Kδ enzyme results in Activated PI3 kinase delta syndrome (APDS). This childhood onset, autosomal dominant, combined immunodeficiency, is caused by heterozygous gain of function (GOF) mutations in PIK3CD (encodes PI3Kδ catalytic subunit p110δ), mutations in PIK3R1 (encodes PI3Kδ regulatory subunit p85α) or LOF mutations in PTEN (terminates PI3Kδ signalling) leading to APDS1, APDS2 and APDS-Like (APDS-L), respectively. APDS was initially described in 2013 and over 285 cases have now been reported. Prompt diagnosis of APDS is beneficial as targeted pharmacological therapies such as sirolimus and potentially PI3Kδ inhibitors can be administered. In this review, we provide an update on the clinical and laboratory features of this primary immunodeficiency. We discuss the common manifestations such as sinopulmonary infections, bronchiectasis, lymphoproliferation, susceptibility to herpesvirus, malignancy, as well as more rare non-immune features such as short stature and neurodevelopmental abnormalities. Laboratory characteristics, such as antibody deficiency and B cell and T cell, phenotypes are also summarised.